IMPERIALISM, SOCIAL INEQUALITY, AND THE POTENTIAL DANGERS OF SCIENTIFIC PROGRESS IN WELLS’ "MEN LIKE GODS" - Tchaparian, Vicky (Armenian Folia Anglistika, 2025)
Wells’ science fiction novel Men Like Gods (1923) explores themes of utopian societies, human nature, and the potential for societal transformation. It comments on issues such as imperialism, social inequality, and the probable dangers of scientific progress. The Utopian world he had created, The Island, includes an advanced society where humans live in an idyllic state of equality, peace, and technological sophistication. The inhabitants of The Island, known as Men Like Gods, have transcended many of the social and political issues that plague the Earth’s societies. The novel presents travelers who are transported to a technologically advanced world where the society is balanced and free from the destructive technological influences that exist in our own world.